2020
DOI: 10.1097/qai.0000000000002504
|View full text |Cite
|
Sign up to set email alerts
|

HIV Stigma and Viral Suppression Among People Living With HIV in the Context of Universal Test and Treat: Analysis of Data From the HPTN 071 (PopART) Trial in Zambia and South Africa

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…HIV stigma remains an ever-present issue affecting progress toward the 95-95-95 targets in sub-Saharan Africa [ 37 , 38 ]. Similar to prior research on decentralized ART delivery [ 39 ], our study indicates that CCMDD may help to decrease HIV stigma concerns, because CCMDD integrates medication refills across chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…HIV stigma remains an ever-present issue affecting progress toward the 95-95-95 targets in sub-Saharan Africa [ 37 , 38 ]. Similar to prior research on decentralized ART delivery [ 39 ], our study indicates that CCMDD may help to decrease HIV stigma concerns, because CCMDD integrates medication refills across chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction and elimination of HIV-related stigma and discrimination (i.e., directed to PLHIV or to key populations at risk of HIV or held by service providers) refers to at least 3 different manifestations: community level discrimination, healthcare provider discrimination, and internalized stigma. Studies have measured the effects of internalized stigma on access to care and treatment and found that it leads to reduced likelihood of testing for HIV [ 19 ], late linkage to care [ 20 , 21 ], lower levels of adherence to treatment [ 22 ], and lower levels of viral suppression among those on treatment [ 23 ]. We have used these studies to estimate the effects of internalized stigma on the treatment cascade: knowledge of status on treatment and viral suppression.…”
Section: Methodsmentioning
confidence: 99%
“…Only two studies examined the link between key population specific stigma and discrimination and HIV outcomes, one with female sex workers [ 43 ] and one with gay men and other men who have sex with men [ 32 ]. The evidence reviewed from 12 studies and 3 systematic reviews found a negative impact of HIV and key population stigma and discrimination on linkage to HIV care [ 33 , 41 ], HIV testing among the general population [ 30 , 42 ], HIV testing among the lesbian, gay, bisexual, and transgender community [ 32 , 34 ], viral suppression [ 31 , 35 , 37 , 38 , 44 ], treatment adherence [ 29 , 36 , 39 ] and treatment initiation [ 41 ]. Experienced stigma in the healthcare setting was also linked with avoiding or delaying care seeking for HIV [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, people living with HIV who perceived high HIV stigma were twice as likely to delay enrolment in HIV care than those who perceived low HIV stigma [ 33 ] and men who have sex with men who reported stigma related to being gay had reduced odds of HIV testing [ 32 ]. Internalized stigma also impedes ART adherence among people living with HIV and key populations by compromising social support and adaptive coping [ 39 , 43 ], and has been linked to poorer viral suppression among people living with HIV who are taking antiretroviral therapy (ART) [ 35 , 37 , 38 , 44 ]. Among female sex workers living with HIV, experienced discrimination related to being a sex worker was associated with higher odds of ART interruption [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation